Entre a prática organizacional e a percepção de trabalhadores : estudo de casos múltiplos sobre gestão sustentável de recursos humanos - Luchi, Raíssa (2024)
This research aims to understand how the practices of Sustainable Human Resource Management are articulated in organizations of the retail sector and how they are perceived by their workers. Theoretical assumptions were used that deal with sustainability, its connection with people management, which is translated into practices, and the respective perception of workers, that corresponds to the process of sense-building in the environment through the interpretation of sensory impressions. For this, a qualitative research was carried out, of descriptive and interpretative character, under the strategy of investigation of multiple case studies, combining documentary analysis techniques and semi-structured interviews to three groups of participants: strategic HR management, HR tactical representatives and workers. The Alfa and Beta cases were selected considering the size of the companies, being the first one in the retail market and the second one in the automotive sector. The data was analyzed by thematic analysis, resulting in the creation of themes and sub-topics that directed the discussion. The development of research points out that strategic HR directors in organizations are still linked to financial objectives and that the integration of sustainability into HR is still a process under construction; the study also indicates that companies make continuous attempts to internalize sustainability in their processes and, finally, it is inferred that workers perceive the implemented practices. However, it is emphasized that some of the main barriers are the understanding about sustainability and the strength of the HR system